TIMP4 Modulates ER-α Signalling in MCF7 Breast Cancer Cells - Pruefer, F; Vazquez-Santillan, K; Munoz-Galindo, L; Cruz-Colin, J L; Maldonado, V; Melendez-Zajgla, J (Folia biologica, 2016)
Tissue inhibitor of metalloprotease 4 (TIMP4) contributes to poor prognosis in breast and other tumours. However, the mechanisms of how TIMP4 influences breast cancer cell behaviour are unknown. Our aim was to explore the signalling pathways modulated by TIMP4 in breast cancer cells. Human recombinant TIMP4 was added to MCF7 breast cancer cells and RNASeq was performed. TIMP4 RNASeq results were validated by RT-PCR. Network analyses of TIMP4-exposed cells showed that ER-α, HIF1A and TGF-β signalling were activated, whereas FOXO3 signalling was downregulated. ER-α protein levels were increased and concordantly, promoters of TIMP4-upregulated genes were significantly enriched in oestrogen-binding sites. We concluded that TIMP4 modulates multiple signalling pathways relevant in cancer in MCF7 cells, including the ER-α cascade.
Keywords: signální transdukce; Signal Transduction; MFC-7 buňky; regulace genové exprese u nádorů; Humans; Tissue Inhibitor of Metalloproteinase-4; Female; tkáňový inhibitor metaloproteinasy 4; tkáňové inhibitory metaloproteinas; Blotting, Western; lidé; Recombinant Proteins; rekombinantní proteiny; Breast Neoplasms; ženské pohlaví; Tissue Inhibitor of Metalloproteinases; Estrogen Receptor alpha; alfa receptor estrogenů; nádory prsu; Real-Time Polymerase Chain Reaction; western blotting; Gene Expression Regulation, Neoplastic; kvantitativní polymerázová řetězová reakce; MCF-7 Cells